The extinction of the quina tree due to agricultural activity concerning the story «Los polvos de la condesa» - Rosas Carbajal, Josselyn Yessenia (2022)
This article will present the results of research into the causes and consequences of the near extinction of the quina tree due to agricultural activity, based on the relevance of this tree as recorded in the story «Los polvos de la condesa», by Ricardo Palma. We will also analyze the properties of quina in the field of medicine from the time of viceregal Peru, when it was used for the different pathologies of the time, to the present day. We are interested in highlighting the importance of disseminating information about the quina tree to preserve it from agricultural activities that are carried out in an indiscriminate and unconscious manner, and which cause the quina tree to be at risk of near extinction.